The Impact of Infrastructure of South Cross Road Line Toward Land Value - Lustina Fajar Prastiwi; Inayati Nuraini Dwiputri (Optimum: Jurnal Ekonomi dan Pembangunan, 2021)
Land is one of the production factors in an economical activity. The demand for a new property is never low, while its existence is limited. This research was conducted in Purwosari Sub-district, Gunungkidul Regency, DIY Province. The researcher chose four villages to did this research, they are Giriasih Village, Girijati Village, Giripurwo Village, and Giricahyo Village. Those villages located in the Sewu Mountain area, Gunungkidul, near Parangtritis Beach. They are passed by JJLS infrastructure project. The purpose of the research is to identify the impact of JJLS project on the pattern of the land value surround 2016. Furthermore, the researcher aims to find the factors behind. Explorative research is used as the research design in this research. The primary data source gained from a measurement using Google Earth software. The secondary data is based on property purchase transaction recording from BKAD Gunungkidul. Thus, the data type is cross-sectional of the land transaction in 2016. This was done by using convenience sampling. The findings of the research show that there is a weakening of 1.5% per kilometers for property which is far away from JJLS. The highness price of the land influenced by some factors, such as land area (4,68%), the distance to CBD (0,0535%), the type of field land (3,65%), and the adequate accessibility (2,96%).